Genotoxicity and Mutagenicity Mechanisms and Test Methods - Soloneski, Sonia; Larramendy, Marcelo L. (IntechOpen, 2021)
This edited book, "Genotoxicity and Mutagenicity - Mechanisms and Test Methods", aims to present the latest developments from different fields, highlighting the detrimental influence that mutagenic and genotoxic agents inflict on DNA and how antimutagenic and anticarcinogenic modulators are able to reduce the negative impact of such toxic agents on living species.